Identification of 4-methyl-5-oxo-octane-1, 8-dioic acid and the derivatives as metabolites of steroidal C, D-ring degradation in Comamonas testosteroni TA441. Issue 185 (January 2019) - Horinouchi, Masae; Malon, Michal; Hirota, Hiroshi; Hayashi, Toshiaki
Highlights: 4-Methyl-5-oxo-octane-1, 8-dioic acid was isolated as a metabolite of steroid degradation in Comamonas testosteroni. Experiments indicated that 4-methyl-5-oxo-2-octene-1, 8-dioic acid was also a metabolite. ORF3( scdN )-encoded CoA-hydratase was indicated to convert CoA-ester of 4-methyl-5-oxo-2-octene-1, 8-dioic acid. Abstract: Comamonas testosteroni TA441 degrades steroids via 9, 17-dioxo-1, 2, 3, 4, 10, 19-hexanorandrostan-5-oic acid, which is presumed to be further degraded by β-oxidation. In the β-oxidation process, Coenzyme A (CoA)-ester of 9-oxo-1, 2, 3, 4, 5, 6, 10, 19-octanor-13, 17-secoandrost-8(14)-ene-7, 17-dioic acid is produced and converted by β-ketoacyl-CoA-transferase encoded by ORF1 and ORF2 ( scdL1L2 ) to cleave the remaining C-ring. In this study, we isolated and identified 4-methyl-5-oxo-octane-1, 8-dioic acid and 4-methyl-5-oxo-3-octene-1, 8-dioic acid from the culture of the ORF3 ( scdN )-null mutant as metabolites of steroid degradation (ADD and cholic acid analogues; cholic acid, chenodeoxycholic acid, deoxycholic acid, and lithocholic acid). In addition of these compounds, UHPLC/MS analysis of the culture of the scdN -null mutant revealed significant accumulation of another compound, which was detected as a dominant peak of m/z 155 ([M−CO2 ] − ) accompanied by a small peak of parental ion ( m/z 199 [M − ]). On the bases of experimental data, this compound was presumed to be 4-methyl-5-oxo-2-octene-1, 8-dioic acid, whose CoA-ester was indicated to be converted by scdN -encoded CoA-hydratase into the CoA-ester of 3-hydroxy-4-methyl-5-oxooctan-1, 7-carboxylic acid.